2015
DOI: 10.1097/anc.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Got Milk? Effects of Early Enteral Feedings in Patients With Gastroschisis

Abstract: Consideration for future studies include incorporating strategies that combine early enteral feeding initiatives with interventions that allow for quicker onset of full enteral intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
11
1
1
Order By: Relevance
“…Although we did not identify nutrition delivery characteristics that were associated with WAZ or decline in WAZ between birth and discharge, the time to achieving enteral autonomy remains a potentially important outcome. PN dependence is associated with increased CLABSI risk, cholestasis, longer length of stay, and intestinal failure . Interestingly in our cohort, time to initiation of EN was not independently associated with time to enteral autonomy when also considering prematurity, atresia, CLABSI, and type of closure.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Although we did not identify nutrition delivery characteristics that were associated with WAZ or decline in WAZ between birth and discharge, the time to achieving enteral autonomy remains a potentially important outcome. PN dependence is associated with increased CLABSI risk, cholestasis, longer length of stay, and intestinal failure . Interestingly in our cohort, time to initiation of EN was not independently associated with time to enteral autonomy when also considering prematurity, atresia, CLABSI, and type of closure.…”
Section: Discussioncontrasting
confidence: 50%
“…PN dependence is associated with increased CLABSI risk, cholestasis, longer length of stay, and intestinal failure. 8,22,25 Interestingly in our cohort, time to initiation of EN was not independently associated with time to enteral autonomy when also considering prematurity, atresia, CLABSI, and type of closure. Other studies have suggested that protocolized feeding with earlier initiation of EN, at around day 7 of life or 1 week after abdominal closure, may be associated with shorter PN dependence and length of stay.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations